2021
DOI: 10.3390/toxins13100678
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Aspergillus Fungi and Recent Aflatoxin Reports, Health Risks, and Advances in Developments of Biological Mitigation Strategies in China

Abstract: Aflatoxins (AFs) are secondary metabolites that represent serious threats to human and animal health. They are mainly produced by strains of the saprophytic fungus Aspergillus flavus, which are abundantly distributed across agricultural commodities. AF contamination is receiving increasing attention by researchers, food producers, and policy makers in China, and several interesting review papers have been published, that mainly focused on occurrences of AFs in agricultural commodities in China. The goal of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…This toxin biosynthesis is a complex process involving at least 27 enzymes, with genetic analysis revealing similarities among aflatoxin-producing fungi [ 29 ]. Furthermore, around 30 genes are known to be crucial for aflatoxin synthesis [ 30 ].…”
Section: Afs and Fungal Producersmentioning
confidence: 99%
“…This toxin biosynthesis is a complex process involving at least 27 enzymes, with genetic analysis revealing similarities among aflatoxin-producing fungi [ 29 ]. Furthermore, around 30 genes are known to be crucial for aflatoxin synthesis [ 30 ].…”
Section: Afs and Fungal Producersmentioning
confidence: 99%
“…Their applications are different in many eras like food, drugs and environmental. In food technology particularly, the chemical and biological contaminants must be determined as they are so crucial in food quality and safety (Mamo et al , 2021; Mishra et al , 2018).…”
Section: Biosensorsmentioning
confidence: 99%
“…Several studies reported health problems after aflatoxin exposure in humans. The major concerns of aflatoxin exposure and accumulation are as the following: serious liver damage, hepatocellular carcinoma and high cirrhosis risk after (Mamo et al , 2021); inducing immunosuppression that would lead in high infections occurrence in human (Zhang et al , 2020); and children growth impairment (Chen et al , 2020). …”
Section: Introductionmentioning
confidence: 99%
“…Especially in recent years, the existence of exogenous harmful substances such as foodborne mycotoxins (FMs) [ 5 , 6 ], which affect the safety of TCMs, have caused international doubts about the safety, effectiveness and quality control of TCMs. Mycotoxins are secondary metabolites produced by fungal organisms [ 7 , 8 ], they have a wide range of sources and have three toxic effects. The WTO designates aflatoxin B 1 (AFB 1 ) as a class I carcinogen [ [9] , [10] , [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%